2015
DOI: 10.1038/srep08742
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of accumulation patterns and preliminary study on the condensation mechanism of proanthocyanidins in the tea plant [Camellia sinensis]

Abstract: In the present study, proanthocyanidins were qualitatively and quantitatively identified using hydrolysis and thiolysis assays, NP-HPLC, HPLC-ESI-MS, MALDI-TOF-MS, 1H-NMR, and 13C-NMR techniques in different organs of tea plants. The results showed that in leaves, the tri-hydroxyl, cis- and galloylated flavan-3-ols were the main monomeric catechins units, and (epi)catechin was found to be the major unit of polymeric flavan-3-ols when the degree of polymerization was greater than five. In roots, the PAs were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 70 publications
(131 reference statements)
4
63
0
Order By: Relevance
“…Peaks 9 and 12 (Figure ) corresponding to ESI − m/z 289 indicated catechin and epicatechin, respectively, and their structures were confirmed by HPLC spiking experiments with the respective standards (Table ). The wide separation of these 2 stereoisomers under HPLC has been reported before (Sun and others ; Jiang and others ).…”
Section: Resultssupporting
confidence: 64%
“…Peaks 9 and 12 (Figure ) corresponding to ESI − m/z 289 indicated catechin and epicatechin, respectively, and their structures were confirmed by HPLC spiking experiments with the respective standards (Table ). The wide separation of these 2 stereoisomers under HPLC has been reported before (Sun and others ; Jiang and others ).…”
Section: Resultssupporting
confidence: 64%
“…Therefore, these compounds are less detected in the full‐fermented or postfermented teas. By using liquid chromatography–mass spectrometry (LC–MS) analysis, the predominant compounds in various processed teas were shown to be flavan‐3‐ols, which provide the intrinsic taste of teas (Beecher, ; Jiang et al., ).…”
Section: Tea Chemistrymentioning
confidence: 99%
“…Flavonoid glycosides are the minor compounds of various teas, but also contribute to the color and taste of tea infusion. Total content of glycosylated flavonoids in green and black tea is about 2.32 to 5.67 g/kg, which is much less than those of catechins (Jiang et al., ).…”
Section: Tea Chemistrymentioning
confidence: 99%
“…As a consequence, the average DP (degree of polymerization) is estimated to be around 4 and 5. It has been reported that procyanidin isolated from Camellia sinensis had 5.44 of average DP [22]. DP of the condensed tannins isolated from tea mangrove seems to be slightly lower than C. sinensis.…”
Section: Isolation and Structure Identificationmentioning
confidence: 99%